Service Quality in Early Intervention Centres: An Analysis of Its Influence on Satisfaction and Family Quality of Life - Jemes Campana, Inmaculada Concepción; Romero-Galisteo, Rita Pilar; Gálvez Ruiz, Pablo; Labajos-Manzanares, María Teresa; Moreno-Morales, Noelia (MDPI, 2021)
Early Intervention (EI) is a set of interventions focused on responding to the needs of children with or at risk of developmental problems. This study aimed to investigate the relationships between the perceived quality of service, satisfaction and family quality of life. Methods: to conduct a multi-centre, transversal study with a non-probabilistic sample. The participants (N = 1551) were families from 24 Early Intervention Centres (EICs) located in Spain. Results: The results indicated an adequate fit of the measurement and structural models, with the latter showing a capacity of 73% to predict the family quality of life. The structural model established that the perceived service quality was a positive and significant predictor of satisfaction (β = 0.85; p < 0.001). Both the perceived quality of service (β = 0.28; p < 0.001) and satisfaction (β = 0.33; p < 0.001) obtained a similar positive and significant relationship with family quality of life, which was slightly stronger than satisfaction. Conclusions: This study provided a better understanding of the importance of the services offered in EICs and their influence on the satisfaction and family quality of life of their users. Thus, delving into these relationships was highly relevant for decision-making in the context of EI.
Keywords: Estimulación precoz; Niños - Desarrollo; Early intervention centres; Perceived quality of service; Family; Quality of life; Satisfaction